IMMUNOCOMPETENT LIVER CELLS REACTION TO INHIBITION OF LUTEINIZING HORMONE SYNTHESIS ON THE 180TH DAY - Rud, M.V.; Shepitko, V.I.; Stetsuk, Ye.V.; Sydorenko, A.G.; Voloshyna, O.V.; Starchenko, І.І.; Nalyvaiko, A.O. (World of Medicine and Biology, 2023)
Hepatic macrophages play a central role in maintaining liver homeostasis and in the pathogenesis of liver injury. Liver macrophages are composed of functionally distinct cellular subpopulations. Currently, there is interest in the effect of androgens and their receptors on different liver cells and the development of liver pathology as well as the potential impact of quercetin on androgen synthesis inhibition. The blockade of luteinising hormone synthesis by administration of triptorelin acetate on day 180 of the experiment caused morphological changes in the structure of the rat liver, in particular in the cellular, connective tissue and vascular components. Total activity of NO synthases in the liver rose up as well as nitrite concentration. Arginase activity was decreased. Administration of quercetin leads to a decrease in the total activity of NO synthases. The shift in macrophage polarization toward the predominance of M1 may be a consequence of endothelial dysfunction as a result of luteinizing hormone synthesis inhibition.
Keywords: liver; macrophage; luteinizing hormone; triptorelin; quercetin; rats